2016
DOI: 10.1371/journal.ppat.1005405
|View full text |Cite
|
Sign up to set email alerts
|

A Viral microRNA Cluster Regulates the Expression of PTEN, p27 and of a bcl-2 Homolog

Abstract: The Epstein-Barr virus (EBV) infects and transforms B-lymphocytes with high efficiency. This process requires expression of the viral latent proteins and of the 3 miR-BHRF1 microRNAs. Here we show that B-cells infected by a virus that lacks these non-coding RNAs (Δ123) grew more slowly between day 5 and day 20, relative to wild type controls. This effect could be ascribed to a reduced S phase entry combined with a moderately increased apoptosis rate. Whilst the first phenotypic trait was consistent with an enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 48 publications
(87 reference statements)
2
48
0
Order By: Relevance
“…In contrast, Seto et al (2010), who blocked miRNA expression by scrambling the three miR-BHRF1 miRNA sequences in a way that would also inactivate the two potential splice donors present in miR-BHRF2*, actually saw an ~2-fold increase in BHRF1 mRNA expression. These results are consistent with the hypothesis that it is the mutation introduced into the miR-BHRF1-2 pre-miRNA stem-loop in the Δ123 EBV mutant, rather than loss of miR-BHRF1-2 or 1-2* expression per se , that results in the reduced level of BHRF1 mRNA and protein expression in the Δ123 LCLs reported by Bernhardt et al (2016).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, Seto et al (2010), who blocked miRNA expression by scrambling the three miR-BHRF1 miRNA sequences in a way that would also inactivate the two potential splice donors present in miR-BHRF2*, actually saw an ~2-fold increase in BHRF1 mRNA expression. These results are consistent with the hypothesis that it is the mutation introduced into the miR-BHRF1-2 pre-miRNA stem-loop in the Δ123 EBV mutant, rather than loss of miR-BHRF1-2 or 1-2* expression per se , that results in the reduced level of BHRF1 mRNA and protein expression in the Δ123 LCLs reported by Bernhardt et al (2016).…”
Section: Resultssupporting
confidence: 91%
“…Whether this novel splicing event has any effect on EBV gene expression is unclear, though it clearly has the potential to inhibit BHRF1 protein expression. In this context, we note that Bernhardt et al (2016) reported that the Δ123 EBV mutant used in this manuscript expresses a far lower level of the BHRF1 protein, and a 5- to 10-fold lower level of BHRF1 mRNA, in LCLs early after EBV infection. In contrast, Seto et al (2010), who blocked miRNA expression by scrambling the three miR-BHRF1 miRNA sequences in a way that would also inactivate the two potential splice donors present in miR-BHRF2*, actually saw an ~2-fold increase in BHRF1 mRNA expression.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…miR-155 could promote the expansion of B cells in vivo (40), and play a critical role in immunity and inflammation in macrophages (41). Interestingly, PTEN, a negative regulator of PI3K-AKT pathway, is a target of miR-155 and BHRF1 miR-cluster of EBV, another malignant herpesvirus (42). …”
Section: Discussionmentioning
confidence: 99%
“…During viral infection, virus-coding miRNAs can also target PTEN to regulate anti-viral immune responses. 50 …”
Section: Functions Of Tumor Suppressor Pten L Chen and D Guomentioning
confidence: 99%